Green Synthesized Chitosan Nanoparticles for Strawberry Micropropagation Protocol - Marwa H M Ubaid; Muslim A A Abdulhussein (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study was conducted to confirm the possibility of obtaining Nano chitosan using green-synthesis technology using aqueous extract of palm fronds and to test adding nano chitosan produced at concentrations of (1.5, 1, 0.5, 0 mg L-1) to the nutrient medium to improve the propagation of strawberry (Fragaria X ananassa) Strawberry Ruby Gem variety. The results of the study showed the possibility of producing nano chitosan particles using green date palm (Zahdi variety) frond extract. The scanning electron microscope (SEM) results showed the formation of spherical shapes with nano-diameters ranging in size from 49.38 to 35.36 and 26.54 nm at an average of 37.08. This was consistent with the results of the UV-Vis spectroscopy, which showed the appearance of the highest peak of chitosan nanoparticles at a wavelength of 226 nm. The X-ray diffraction study of the produced nano-chitosan showed the absence of clear peaks, confirming that the nano-chitosan is of an amorphous nature. The strawberry micropropagation program was evaluated by adding different concentrations of manufactured nano-chitosan to the strawberry propagation medium at its different stages (sprouting, multiplication and rooting). It was found that the produced nano-chitosan showed a significant effect in reducing the percentage of contamination in the plants and increasing the response rate and the number and length of the branches formed when added at the branch emergence stage. At an advanced stage, adding chitosan to the culture medium led to improving the characteristics of Vegetative growth in number of branches, lengths, number of leaves, fresh and dry weight were significantly different from those obtained from the standard medium. It was also observed that the manufactured nano chitosan recorded the highest rooting percentage and the highest rate of number and length of roots when it was added to the rooting medium.